2020
DOI: 10.1002/pca.2911
|View full text |Cite
|
Sign up to set email alerts
|

1H‐NMR metabolomics profiling of recombinant tobacco plants holding a promoter of a sesquiterpene cyclase

Abstract: Introduction Nicotiana tabacum is a plant model intensively used in the bio‐engineering pharmaceutical industry as a platform to produce drugs and therapeutic agents. Currently, no information regarding the non‐targeted metabolome of transgenic tobacco containing recombinant regulatory sequences is available. Objective To compare the proton nuclear magnetic resonance (1H‐NMR) metabolomics profiling of a recombinant Nicotiana tabacum strain containing a promoter of a sesquiterpene cyclase from Capsicum annuum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The first one could involve the colonization of saprophytic microorganisms such as yeasts which convert assimilable sugars into methanol. [22] The second is regarded to the degradation of cell walls leading to the hydrolysis of cell polysaccharides to produce methanol. [14] Previous studies revealed that plants subjected to chronic stress such as those containing recombinant DNA, can accumulate high amounts of methanol.…”
Section: Implications For Secondary Metabolismmentioning
confidence: 99%
“…The first one could involve the colonization of saprophytic microorganisms such as yeasts which convert assimilable sugars into methanol. [22] The second is regarded to the degradation of cell walls leading to the hydrolysis of cell polysaccharides to produce methanol. [14] Previous studies revealed that plants subjected to chronic stress such as those containing recombinant DNA, can accumulate high amounts of methanol.…”
Section: Implications For Secondary Metabolismmentioning
confidence: 99%
“…Validation was done with the R 2 x and Q 2 values using 999 permutations analysis and performed with SIMCA ver. 16.0 [77].…”
Section: Chemometrics Analysismentioning
confidence: 99%
“…In addition, tobacco also has important significance to humans for their ornamental values and medicinal uses [2]. In recent years, many bioactive naturally small molecule metabolites have been reported from this genus, including diterpenoids [3], sesquiterpenoids [4,5], flavonoids [6,7], coumarins [8,9], furans [10,11], alkaloids [12,13], sterols [6], and the like. The biosynthesis and pharmacological properties of some metabolites also have been widely elucidated, such as pyridine alkaloids, including the eponymous nicotine [14], isoprenoids [15], aromatic compounds [16], and polyphenols [17].…”
Section: Introductionmentioning
confidence: 99%
“…Fig 3. Plausible biosynthetic pathway of the oxocyclopentane moieties in nicoisoindoles A-D(1)(2)(3)(4) …”
mentioning
confidence: 99%